Outcome of carotid artery stenting in the hands of vascular surgeons - Hoffmann-Wieker, Carola Marie; Demirel, Serdar; Attigah, Nicolas; Hakimi, Maani; Böckler, Dittmar (Langenbeck's archives of surgery, 2017)
ObjectivesTo analyze the procedural and clinical outcomes of carotid artery stenting (CAS) in the hands of endovascular trained vascular surgeons.MethodsBetween April 2008 to May 2013, 1197 patients were treated for extracranial internal carotid artery (ICA) stenosis. The proportion of endovascular treated patients was 5.0% (CAS n = 60 vs. carotid endarterectomy (CEA) n = 1137). All patients in the CAS group (44 males, median age 70 years) were treated by two senior vascular surgeons experienced in endovascular methods. Restenosis was the indication for CAS in 32 out of 60 patients (53.3%). Further indications were contralateral ICA occlusion (n = 14, 23.3%), radiogenic ICA stenosis (n = 5, 8.3%), high-risk candidates for CEA (n = 4, 6.6%), and the presence of contralateral recurrent paresis (n = 2, 3.3%). High-risk patients for CEA were defined as patients with history of severe cardiac disease and patients with impaired general condition. 84.4% (n = 27) of the restenosis were asymptomatic with a mean degree of stenosis of 83.7%, and 12.9% (n = 4) were symptomatic (degree of stenosis of 90%). Mean procedural and fluoroscopy time were 61 and 14 min. Study endpoints were periprocedural stroke-related mortality and morbidity, restenosis rate, and overall survival. Follow-up was performed by duplex ultrasound with a median follow-up period of 12 months (range 1-55).ResultsThe periprocedural stroke rate of CAS within 30 days was 3.3% (one ischemic stroke, one intracranial hemorrhage); two additional patients suffered TIA (3.3%). None of the patients had a myocardial infarction perioperatively. The mortality rate was 0. CAS procedures were completed in 90.0% (n = 54) of cases. Dropout rate was 8.3% (n = 5) for morphological reasons (e.g., carotid kinking). Intraoperative complication rate was 1.7% (n = 1) including one patient who suffered intraoperative rupture of access vessels. The conversion rate with subsequent CEA procedure was 6.6% (n = 4 of 5). The restenosis rate during follow-up was 3.3% after CAS. The reintervention rate during the median follow-up period of 12 months (1-55 months) was 5.5% (n = 3/54). Two patients received a reintervention with successful balloon angioplasty; in one case, a diagnostic angiography was performed excluding the presence of a relevant restenosis. No additional stent was implanted. The survival rate was 100% at 1 year, 90.4% at 2 years, and 77.7% at 3 years.ConclusionCAS, in the hands of vascular surgeons, is feasible with a moderate perioperative risk in a highly selected patient cohort. A procedure termination rate of approximately 10% shows that the complementary therapy using CAS procedure is not overused by surgeons.